Chapter L'Asia orientale vista con gli occhi di viaggiatori italiani del secolo XVI - ROSA, Cristina (Studi e saggi, 2021)
The Italian travellers to the East during the 16th century left us some important works that they elaborated after their return to their homeland, works whose declared motivation was not only to leave a tangible memory of their life experiences but also to offer the cultured public of Old Europe and people interested in those geographical areas for professional reasons, useful material for a better understanding of the world. These texts, produced in accordance with certain literary canons that were already relatively well defined, are often documents capable of testifying to travel experiences in the era of the great geographical explorations in the Far East after Vasco da Gama's voyage.